Determination of weathering rate of the Morro do Ferro Th-REEs deposit, Brazil using U-isotope method - Bonotto, Daniel Marcos [UNESP]; Fujimori, K.; Moreira-Nordemann, L. M. (Elsevier B.V., 2007)
The weathering rate was estimated by changes in U-214/U-238 activity ratio (AR) and U content of rocks, borehole spoil and surface water samples at the Morro do Ferro Th-REEs deposit. The deposit is situated in the Pocos de Caldas alkaline massif, Brazil. The south stream basin investigated in this paper has not been significantly affected by anthropogenic inputs of pollutants as compared to the Corumbatai River basin in São Paulo State, where the method was previously applied. The weathering rate derived utilizing the Uisotopes modeling corresponded to 0.015 mm/yr (67,000 years to weather 1 m ofrock under the actual climatic conditions). The estimated rate is very reasonable in comparison with the range of 0.015-0.05 mm/yr of land surface lowering within the entire caldera. It is also compatible with a rate of 0.013 mm/yr determined for the Salgado River basin in a semi-arid region in Bahia State, Brazil. The value generated is reliable and increases the potential use of the method for other different areas in Brazil and elsewhere, because it may be used in regions with different climatic conditions and (un)polluted basins. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: weathering rate; uranium isotopes; Th-REEs deposit; Pocos de Caldas plateau; Brazil